Investigating Students’ Difficulties in Mastering English Listening Skills - Nurul Aulia; Ali Akbarjono; Feny Martina (International Journal of Innovation and Education Research, 2023)
This research aimed to find out the difficulties of students in mastering English listening skills at one of non-goverment MTs Bengkulu Tengah. This his study employed descriptive qualitative research method. The research subjects in this study are students at VII A Class of MTs Panca Mukti Bengkulu Tengah as the primary data source with the total subjects are 35 Students. The instruments used to collect the data in this research were observation, interview and documentation. The Semi Structured Interview consists of 12 questions. The researcher observed the class, after that, the researcher choosed fifteen students who had most difficulties in listening to be interviewed. The results of this study showed that the difficulties that the students faced in listening were related into four categories namely students’ difficulties related to the listening material, students’ difficulties related to the speaker, students’ difficulties related to the listener, students’ difficulties related to the physical environment. Besides, the factors which cause students’ difficulties in listening were lack of vocabulary, having hearing problems, unfocussed, the speaker spoke too fast.